Strategi guru pembelajaran guru PAI dalam menangani kemunduran karakter siswa di SMP N 03 Randublatung Blora - Aisyah Kresnaningtyas; Naimatus Tsaniyah (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2020)
This research uses a qualitative approach. Data collection techniques there are methods used,Â Namely, observation, documentation, and interviews. The data analysis uses there stages namely, data reduction, data presentation, data verification and drawing conclusions from the results of the study. Respondents who were the source of information were the principal, counseling, guidance teacher, student for students, PAI Teacher and Student, PAI Teacher and Students. The results of this study can concluded as Follows: (1) the exemplary strategy, (2) the advice strategy, (3) confidence, and control, the reward and punishment strategy